Reduced versus standard dose apixaban for secondary prevention of cancer-associated venous thromboembolism: A systematic review and meta-analysis - Malhotra, Vasu; Patel, Shreya G.; Feinaj, Ardit; Amin, Devesh; Ash, Henry; Boozo, Mohammad B.; Breslow, Zachary; Trube, Jennifer; Farooq, Muhammad Z.; Sabina, Michael (Frontiers in Oncology, 2025)
Patients with cancer-associated venous thromboembolism (VTE) often require prolonged anticoagulation because malignancy and chemotherapy can persist for months to years, sustaining both thrombotic and bleeding risks. While full-dose apixaban (5 mg twice daily) is recommended for secondary prevention, extended use may increase bleeding in this vulnerable population. Reducing the dose to 2.5 mg twice daily after six months of full-dose treatment has been proposed to lower bleeding risk without compromising protection against recurrent VTE. To clarify the safety and efficacy of this strategy, we conducted a meta-analysis of randomized controlled trials comparing reduced- versus standard-dose apixaban for extended therapy in patients with cancer-associated VTE. The study followed PRISMA guidelines and was registered in PROSPERO (CRD420251026337). Hazard ratios and risk ratios with 95% confidence intervals were pooled using a random-effects model, and evidence certainty was assessed with GRADE. Two randomized trials comprising 2,126 patients (EVE, n = 360; API-CAT, n = 1,766) met inclusion criteria. The composite outcome of recurrent VTE with bleeding showed a significantly lower risk with reduced-dose apixaban (risk ratio 0.79, 95% CI 0.65–0.96; I2 = 0%), and the composite of major and clinically relevant nonmajor bleeding was also reduced (HR 0.75 (95% CI 0.63–0.88; I2 = 0%). No significant differences were observed for recurrent VTE, major bleeding, clinically relevant nonmajor bleeding, mortality, deep-vein thrombosis, or pulmonary embolism. These findings indicate that reduced-dose apixaban after the initial six months of anticoagulation decreases bleeding without loss of efficacy, supporting dose de-escalation as a safe, evidence-based approach for extended anticoagulation in cancer-associated VTE.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier PROSPERO CRD420251026337.